Gardenia jasminoides Ellis Fruit Extracts Attenuated Colitis in 2, 4, 6-Trinitrobenzenesulfonic Acid-Induced Rats. (15th December 2021) - Liu, Jing; Yang, Chao; Wu, Zhigui; Pei, Jianguo; Chen, Yao; Huang, Xiao; Gao, Sha; Kan, Rui; Zhang, Wenna; Xie, Saisai; Fu, Xiaomei
Abstract : Ulcerative colitis (UC) is a relapsing inflammatory disease with an unknown precise etiology. The purpose of this study is to investigate the protective effects of Gardenia jasminoides Ellis fruit extracts (GFE) on 2, 4, 6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats. GFE (50 mg/kg, 100 mg/kg) were administered orally for 7 days after induction. Meanwhile, the chemical components of GFE were performed by UPLC-QTOF-MS/MS. GFE significantly decreased DAI scores and ameliorated macroscopic and histologic damage. It also reduced the levels of MPO, NO, MDA, IL-1 β, TNF- α, and IL-6, while increasing the level of SOD. Moreover, 56 components were identified in GFE using a UPLC-QTOF-MS/MS method, which can be categorized into six structural groups. Our results indicated that GFE has an ameliorative effect on TNBS-induced colitis in rats, which may further verify its anti-inflammatory and antioxidative properties. Therefore, GFE can be a promising protective agent of colitis that deserves further investigation.